Potent Antibacterial Agents: N-Substituted Derivatives of N-(4-Methylpyridin-2-yl)benzenesulfonamide - Rehman, Aziz-ur; Arfan, Muhammad; Athar Abbasi, M.; Nazir, Majid; Rasool, Shahid; Gul, Samreen; Ahmad, Irshad; Afzal, Saira (Asian Journal of Chemistry, 2014)
In the present work, a new series of N-substituted-N-(4-methylpyridin-2-yl)benzenesulfonamides (5a-f), was synthesized and evaluated for antibacterial activity. The synthesis was carried out by the coupling of 2-amino-4-methylpyridine (1) with benzenesulfonyl chloride (2) yielded N-(4-methylpyridin-2-yl)benzenesulfonamide (3) under dynamic pH control of basic aqueous medium of sodium carbonate. Further, the molecule 3 was reacted with different alkyl/aralkyl halides, 4a-f, yielded the products 5a-f, in the presence of N,N-dimethyl formamide and LiH. The proposed structures of synthesized molecules were corroborated by IR, 1H NMR and EI-MS spectral data and also screened for antibacterial activity. All the compounds exhibited moderately good inhibitors and only compound 5e executed no activity against P. aeroginosa, gram-negative bacterial strain.